Pension reforms, economic security, and mental health: The need for a human rights-based approach - Sarah Steele; Milagros Ruiz; Matthew Parbst; David Stuckler (Cambridge Prisms: Global Mental Health)
Pension systems play a crucial role in providing economic security and supporting well-being in later life. However, as governments implement reforms to ensure financial sustainability—such as raising the retirement age, reducing benefits, and shifting to defined-contribution schemes—these measures often overlook their psychological and social consequences. Pension insecurity has been linked to heightened stress, anxiety, and depression, as well as increased social isolation, particularly among vulnerable populations, including those in physically demanding jobs, low-income workers, and individuals with existing health conditions. Despite clear evidence of these effects, mainstream pension reform discourse prioritises fiscal concerns over social and mental health implications. This article examines pension reform through the Human Rights–Public Health Pension Framework (HRPHPF), integrating legal, public health, and policy perspectives to assess its impact on mental well-being. It situates pension rights within international human rights law, explores the psychological risks associated with pension insecurity, and advocates for a human rights-based approach to pension policymaking. The article calls for integrating mental health impact assessments into pension reforms to prevent adverse outcomes and ensure that policies promote dignity, social inclusion, and economic security in old age. A more balanced approach is necessary to align financial sustainability with broader well-being and human rights principles.